2018
DOI: 10.1111/jfb.13868
|View full text |Cite
|
Sign up to set email alerts
|

Change in the dominance structure of two marine‐fish assemblages over three decades

Abstract: Marine fish are an irreplaceable resource, but are currently under threat through overfishing and climate change. To date, most of the emphasis has been on single stocks or populations of economic importance. However, commercially valuable species are embedded in assemblages of many species and there is only limited understanding of the extent to which the structure of whole communities has altered in recent years. Most assemblages are dominated by one or a few species, with these highly abundant species under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Variability in the abundance of commercial catches of fish has been studied for centuries (Huxley, 1881), especially in highly productive and highly populated regions (Heincke, 1898; Newland, 1999). Globally, abundance of fishing stocks has displayed declines over the past several decades (Worm et al, 2009), with changes in commercial fish assemblages identified for important fishing grounds in north‐western Europe (Moyes & Magurran, 2019), in the north‐eastern Pacific (Levin, Holmes, Piner, & Harvey, 2006) and on the Newfoundland/Labrador Shelf (Gomes, Haedrich, & Villagarcia, 1995). Long‐term impacts of fisheries have included over‐exploitation of target species, by‐catch and habitat destruction, fundamentally altering marine ecosystems worldwide (Hinz et al, 2017; Jackson, 2001; MRAG & IEEP, 2007; Pauly, Christensen, Dalsgaard, Froese, & Torres, 1998; Worm et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Variability in the abundance of commercial catches of fish has been studied for centuries (Huxley, 1881), especially in highly productive and highly populated regions (Heincke, 1898; Newland, 1999). Globally, abundance of fishing stocks has displayed declines over the past several decades (Worm et al, 2009), with changes in commercial fish assemblages identified for important fishing grounds in north‐western Europe (Moyes & Magurran, 2019), in the north‐eastern Pacific (Levin, Holmes, Piner, & Harvey, 2006) and on the Newfoundland/Labrador Shelf (Gomes, Haedrich, & Villagarcia, 1995). Long‐term impacts of fisheries have included over‐exploitation of target species, by‐catch and habitat destruction, fundamentally altering marine ecosystems worldwide (Hinz et al, 2017; Jackson, 2001; MRAG & IEEP, 2007; Pauly, Christensen, Dalsgaard, Froese, & Torres, 1998; Worm et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it would be interesting to use a null model approach to examine the interactions between environmental filtering and shifts in assemblage size, particularly when the latter is a response to an increase in carrying capacity linked to climate change. Unravelling the mechanistic links between trends in functional and taxonomic diversity will also be important, in, for instance, discovering the extent to which functional rarity is linked to whether a species is a winner or loser during biodiversity change [ 33 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we observed higher levels of taxonomic rarity relative to the null expectation (figure 3a,b), as well as reduced evenness, for given levels of richness, in the west coast system (figure 3c) as opposed to the east coast system (figure 3d). Since increased taxonomic rarity can be associated with habitat complexity [45][46][47], this result could reflect the increased structural heterogeneity of the west coast, as well as contrasts in warming trends, and/or recovery from historical fishing pressures [33,48]. Historically, the east coast system (North Sea region) has been more heavily exploited than the west coast system (Celtic Sea area), but, since the beginning of this time series in 1985, fishing pressure has been largely similar in both areas (see electronic supplementary material, figure S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-species assemblages of marine animals have been studied, however, most research has focused on invertebrates or fish (Barnes, 2019;Moyes and Magurran, 2019;Palumbi et al, 2019). Large marine vertebrates also maintain multispecies groups (Augé et al, 2018;Drymon et al, 2020;Sutton et al, 2020) and because these species typically inhabit a higher trophic level, changes in habitat may have serious consequences.…”
Section: Introductionmentioning
confidence: 99%